Emerging infectious disease laboratory and diagnostic preparedness to accelerate vaccine development. Issue 10 (3rd October 2019) - Roberts, Christine C.
ABSTRACT: Rapid vaccine development in response to an outbreak of a new emerging infectious disease (EID) is a goal targeted by public health agencies worldwide. This goal becomes more complicated when there are no standardized sets of viral and immunological assays, no accepted and well-characterized samples, standards or reagents, and no approved diagnostic tests for the EID pathogen. The diagnosis of infections is of critical importance to public health, but also in vaccine development in order to track incident infections during clinical trials, to differentiate natural infection responses from those that are vaccine-related and, if called for by study design, to exclude subjects with prior exposure from vaccine efficacy trials. Here we review emerging infectious disease biological standards development, vaccine clinical assay development and trial execution with the recent experiences of MERS-CoV and Zika virus as examples. There is great need to establish, in advance, the standardized reagents, sample panels, controls, and assays to support the rapid advancement of vaccine development efforts in response to EID outbreaks.